2020
DOI: 10.20944/preprints202001.0138.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Endogenous Opioid System in Schizophrenia and Treatment Resistant Schizophrenia: Increased Plasma Endomorphin 2, and κ and μ Opioid Receptors are Associated with Interleukin-6

Abstract: Background: Activation of the immune-inflammatory response system (IRS) and the compensatory immune-regulatory system (CIRS) play a key role in SCZ and treatment resistant SCZ. There are only few data on immune and endogenous opioid system (EOS) interactions in SCZ and treatment resistant SCZ.Aim of the study: We examined serum β-endorphin, endomorphin-2 (EM2), mu-opioid (MOR) and kappa-opioid (KOR) receptors, and interleukin (IL)-6 and IL-10 in 60 non responders to treatment (NRTT), 55 partial RTT (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…[107][108][109] EOS peptides and receptors are secreted during immune activation, and most of them act as CIRS compounds. 26,52,105 In the current study, we observed that lactosylceramide levels significantly increased in RA compared to controls and were marginally associated with the common phenome core extracted from the PP and RA disease activity data. Some ceramides, including CD17, are significantly elevated in depressed patients.…”
Section: Other Biomarkers Of Pp Due To Rasupporting
confidence: 45%
See 1 more Smart Citation
“…[107][108][109] EOS peptides and receptors are secreted during immune activation, and most of them act as CIRS compounds. 26,52,105 In the current study, we observed that lactosylceramide levels significantly increased in RA compared to controls and were marginally associated with the common phenome core extracted from the PP and RA disease activity data. Some ceramides, including CD17, are significantly elevated in depressed patients.…”
Section: Other Biomarkers Of Pp Due To Rasupporting
confidence: 45%
“…52 Activation of immune-inflammatory pathways is likely responsible for circulating levels of β-endorphin and other EOS markers (such as MOR and KOR) during inflammatory conditions. 105,106 Successive expression of chemokines and adhesion molecules, primarily CXCR2 ligands, L and P selectins, α4/β2 integrins, and intercellular adhesion molecule 1 orchestrate the recruitment of opioid-containing leukocytes from the circulation to the site of inflammation. [107][108][109] EOS peptides and receptors are secreted during immune activation, and most of them act as CIRS compounds.…”
Section: Other Biomarkers Of Pp Due To Ramentioning
confidence: 99%
“…Recently, we reviewed that the EOS may contribute to schizophrenia symptomatology and neurocognitive impairments (Moustafa et al, 2020). For example, KOR activators or agonists have psychotomimic properties and may induce hallucinations and negative-like symptoms, neurocognitive deficits and psychomotor retardation (Clark & Abi-Dargham, 2019;Land et al, 2008;Nemeth et al, 2010;Shekhar, 2019).…”
Section: Mechanistic Explanationsmentioning
confidence: 99%
“…Chen et al, 2015;Heinke, Gingl, & Sandkühler, 2011). On the other hand, β-endorphin and MOR have antinoceptive effects and may exert CIRS activities by suppressing the primary immune response in schizophrenia (Moustafa et al, 2020). Future research should examine the EOS in ME/CFS and fibromyalgia to delineate the role of those opioids.…”
Section: Mechanistic Explanationsmentioning
confidence: 99%
See 1 more Smart Citation